Stability of self-assembled hydrophobic surfactant layers in water. - Perkin, S; Kampf, N; Klein, J (2005)
Using contact angle measurements, surface force balance experiments, and AFM imaging, we have investigated the process of self-assembly of surfactants onto mica and the subsequent stability of those layers in pure water. In the case of cetyltrimethylammonium bromide (CTAB), the stability of a monolayer when immersed in pure water is found to be dependent on initial immersion time in surfactant, which is likely to be caused by an increase in the proportion of ion-exchange to ion-pair adsorption when incubated in surfactant for longer periods of time. Infinite dilution of the surfactant solution before withdrawal of the sample is found to have little effect on the stability of the resulting layer in pure water. The nature of the counterion is found to affect dramatically the stability of a self-assembled surfactant monolayer: cetyltrimethylammonium fluoride (CTAF) forms a layer that is much more stable in water than CTAB, which is likely to be due to faster and more complete ion-exchange with the mica surface for CTAF. Surface force balance experiments show that when the hydrophobic monolayer is immersed in pure water it does not simply dissolve into the water; instead it rearranges, possibly to patches of bilayer or hemimicelles. The time scale of this rearrangement agrees well with the time scale of the change from a hydrophobic to more hydrophilic surface observed using contact angle measurements. AFM imaging has also in some cases shown an evolution from an even monolayer to patches of bilayer.